2010
DOI: 10.1177/1538574410374658
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional Results for the Surgical Management of Neurogenic Thoracic Outlet Syndrome

Abstract: Durable long-term functional outcomes can be achieved predicated on a highly selective approach to the surgical management of patients with NTOS. A majority of operated patients will not require adjunctive procedures or chronic narcotic utilization. Patients who undergo surgery can expect to return to work with little or no functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…3,7,8 It could be postulated that, similar to various other complex regional pain syndromes, persistent repetitive stimulation of central pain pathways over time results in autonomous signal generators that could confound results. 4,9 However, to the best of our knowledge, our study is the first to show that this association was more closely associated with age. Each additional month of symptoms in the patient group Ն40 years was associated with a significant decrease in successful outcome.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…3,7,8 It could be postulated that, similar to various other complex regional pain syndromes, persistent repetitive stimulation of central pain pathways over time results in autonomous signal generators that could confound results. 4,9 However, to the best of our knowledge, our study is the first to show that this association was more closely associated with age. Each additional month of symptoms in the patient group Ն40 years was associated with a significant decrease in successful outcome.…”
Section: Discussioncontrasting
confidence: 70%
“…This underscores the importance of careful patient selection by distinguishing between the diagnoses as well as the use of appropriate adjunctive tests to optimize the results of surgical outcomes. [4][5][6] There have been few risk factors and predictors that have been implicated to affect successful surgical outcomes. Among some of the factors that were evaluated in our study included the affect of age, duration of symptoms, and impact of anterior scalene blocks.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This correlates well with that reported elsewhere, 7 with published work noting trauma in 15% to 80%, 19,20 although McCarthy et al did not find this in the history of any of their cohort. 17 We have found that those patients whose etiology included traumatic injury did not demonstrate improved DASH scores postoperatively; in contrast, significant improvement was noted in those who had not reported this as an etiological factor.…”
Section: Discussionsupporting
confidence: 93%